One more flower remains in the Emperor’s bouquet: Bellucia imperialis as a prior name for B. dichotoma (Melastomataceae) - Chagas, Earl Celestino De Oliveira; Costa-Lima, James Lucas Da (Phytotaxa, 2020)
The names Bellucia dichotoma and B. imperialis have been treated as synonyms and both had been considered as published in the same work, the Cogniaux’s monograph for Flora Brasiliensis. Bellucia dichotoma is the currently accepted name and it is widely applied to herbarium specimens and used in some Melastomataceae floristic treatments and South American checklists. However, based on literature review, we detected that the name B. imperialis was effectively published in a work prior to Cogniaux’s monograph, more precisely a year earlier. Therefore, the name B. imperialis should be considered as the correct name. Additionally, we elected a second-step lectotype for the name B. dichotoma.